High efficient vacuum deposited red organic light-emitting diodes compared with their solution-processed counterpart. (2nd September 2017) - Sree, Vijaya Gopalan; Park, Hoyeol; Cho, Woosum; Jin, Sung-Ho
ABSTRACT: Herein, we demonstrate dry- and wet-process feasible red (PhQ-Th)3 Ir complex as dopant and improved external quantum efficiency (EQE) of the device by 30.17% though vacuum-process using the same device structure. The turn-on voltage is reduced to less than 3 V by adopting vacuum deposition process. The vacuum-processed devices showed EQE and power efficiency of 26.75% and 28.90 lm/W, respectively, with turn on voltage of 2.83 V. The maximum luminance is increased from 1088 cd/m 2 to 6396 cd/m 2 using dry-process. It is found that the difference in device performance is attributed to their morphological variance of solution- and vacuum-processed devices.